Non-inferiority of Generic Tenofovir Disoproxil Fumarate/ E mtric itabi ne, Hivent® to Brand Name, Truvada® in HIV-Infected Patients - Mete, Bilgül; Gündüz, Alper; Gencer, Serap; Öztoprak, Nefise; Kurtaran, Behice; Altuntaş Aydın, Özlem; Gümüşer, Fatma; Karabay, Oğuz; Köse, Şükran; Öngürü, Pınar; et al. (Cerrahpaşa Medical Journal, 2022)
Objective: Antiretroviral agents provided a significant improvement in HIV-related mortality. Generic drugs decrease the cost and provide easier access to treatment. However, there are concerns about efficacy and safety. We assessed non-inferiority of generic tenofovir disoproxil fumar ate/ e mtric itabi ne, Hivent® to brand name drug, Truvada® in a retrospective cohort. Methods: Nine centers from Turkey were enrolled and the study included 457 patients followed up between May 2015 and April 2017 with Truvada® (n = 227) and Hivent® (n = 230) in combination with other antiretrovirals. Baseline characteristics were comparable in both groups. Demographic characteristics and laboratory values at baseline and during treatment were recorded. The primary endpoint was virologic response after 12 months of therapy, as determined by Snapshot algorithm from Food and Drug Administration (FDA). The sample size calculation was based on the primary endpoint. Non-inferiority margin was taken as 10%. Results: After 12 months of therapy, both drugs provided a comparable decline in HIV-RNA: The values at baseline, 1st, 3rd, 6th, 9th, and 12th month by Truvada® were 6.32, 3.62, 2.52, 3.53, 3.01, and 1.71 log10 copies/mL, respectively and values by Hivent® were 5.93, 3.89, 2.18, 1.72, 3.63, and 1.54 log10 copies/mL, respectively (P = .33). Both drugs provided a comparable significant increase in CD4+ cell count: values By Truvada® were 338, 412, 472, 497, 511, and 580 cells/mL, respectively and values by Hivent® were 337, 503, 531, 553, 644, and 660 cells/mL (P = .13). The rate and severity of side effects were similar and the changes in biochemical parameters were not different. Conclusion: This retrospective cohort study showed that Hivent® has comparable efficacy and side effect profile and non-inferior to Truvada®. Cite this article as: Mete B, Gündüz A, Gencer S, et al. Non-inferiority of generic tenofovir disoproxil fumar ate/e mtric itabi ne, Hivent® to brand name, Truvada® in HIV-infected patients. Cerrahpaşa Med J. 2022;46(3):238-244.